TEACHNOLOGYINDIGITAL NATIVENESS: ENHANCING TECHNOLOGY AS INVISIBLE MEDIA - Adityo Adityo (Erudio Journal of Educational Innovation, 2015)
In the recent thinking of integrating technology into our educational systems, the quote from Prensky“Today’s students are no longer the people our educational system was designed to teach”, could bring a new horizon when we are, as a teacher, designing  the lesson plan and methods. The role of technology in the 20th century’s in education is undoubtedly brings a major impact on the paradigm of how the teaching activity should or should not be done in accordance to the newest culture, and to implement the newest technology into our teaching activities should be the most critical question to put in mind at present. It is accurately phrased that the role of books and teachers cannot be replaced by technology, but the one who refused to implement the technology will be replaced by the one who adapt.The previous method of teaching is already obsolete and inadequate to be used as the mind-set of the recent educational culture and the people involved inside it is evolving terrifically, therefore, opening our mind to the previously unthinkable way of thinking could be the key to evolve our education.Keyterms: Digital nativeness, technology and media